A Generalized Algorithm for Fast Two-Dimensional Angle Estimation of a Single Source With Uniform Circular Arrays - Bin Liao; Yun-Tao Wu; Shing-Chow Chan (IEEE antennas and wireless propagation letters, 2012)
We reported an algorithm for two-dimensional (2-D) angle estimation of a single source with uniform circular arrays (UCAs) in our previous work. However, it is worth noting that this method is derived based on the assumption that the number of the sensors is even. This may limit its application in practice. To this end, we extend our previous work and propose a generalized algorithm that is applicable to UCAs with the sensor number being even as well as odd. Similar to our previous work, the generalized algorithm offers closed-form estimates of azimuth and elevation angles. Thus, it is computationally efficient. Numerical examples are provided to show the effectiveness and good performance of the proposed generalized approach.